The state and prospects of development of free economic zones in the Republic of Uzbekistan (Zien Journal of Social Sciences and Humanities, 2022)
The article discusses the foreign experience in improving the functioning of free economic zones. In addition, measures to implement a foreign strategy in Uzbekistan were considered.